YBX1 is a modulator of MIA/CD-RAP-dependent chondrogenesis - Schmid, Rainer; Meyer, Katharina; Spang, Rainer; Schittek, Birgit; Bosserhoff, Anja Katrin (PLoS ONE, 2013)
MIA/CD-RAP is a small, secreted protein involved in cartilage differentiation and melanoma progression. We recently revealed that p54 nrb acts as a mediator of MIA/CD-RAP action to promote chondrogenesis and the progression of malignant melanoma. As the molecular mechanism of MIA/CD-RAP action in cartilage has not been defined in detail until now, we aimed to understand the regulation of p54nrb transcription in chondrogenesis. We concentrated on the previously described MIA/CD-RAP-dependent regulatory region in the p54nrb promoter and characterized the transcriptional regulation of p54nrb by MIA/CD-RAP in cartilage. A series of truncated p54nrb promoter constructs and mutagenesis analysis revealed that the transcription factor YBX1, which has not been investigated in chondrogenesis thus far, is the mediator of MIA/CD-RAP dependent activation of p54nrb transcription. A systematic analysis of genes carrying this binding site in their promoter region revealed further potential MIA/CD-RAP-regulated genes that have been implicated in cartilage differentiation. In summary, we described the effects of MIA/CD-RAP on transcriptional regulation in chondrocytes. Understanding the regulation of p54nrb via YBX1 contributes to the understanding of chondrogenesis. Uncovering new downstream effectors that function via the activation of YBX1 supports the important role of MIA/CD-RAP in these processes. © 2013 Schmid et al.
CRIS-Team Scopus Importer:2022-08-05